2017
DOI: 10.3126/hren.v13i1.17943
|View full text |Cite
|
Sign up to set email alerts
|

Impact of educational intervention on knowledge regarding safe handling of cytotoxic drugs among the nursing personnel working in BPKIHS

Abstract: Introduction: Cytotoxic drugs are toxic compounds and are known to have carcinogenic,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The authors used a structured, pre-tested self-administered questionnaire to collect data. The questionnaire was adapted from previous literature 15,19,30,32 comprising of three major sections, namely, section one composed of demographic data of the nurses such as age, sex, educational, marital status, total years' work experience, and training course on chemotherapy. Section two and three consisted of safe handling knowledge and practices of CDs respectively and the availability and utilization of Personal Protective Equipment (PPE).…”
Section: Data Collection and Managementmentioning
confidence: 99%
“…The authors used a structured, pre-tested self-administered questionnaire to collect data. The questionnaire was adapted from previous literature 15,19,30,32 comprising of three major sections, namely, section one composed of demographic data of the nurses such as age, sex, educational, marital status, total years' work experience, and training course on chemotherapy. Section two and three consisted of safe handling knowledge and practices of CDs respectively and the availability and utilization of Personal Protective Equipment (PPE).…”
Section: Data Collection and Managementmentioning
confidence: 99%
“…The results of most studies in this field confirmed the effect of the training interventions on nurses' knowledge and performance.For example, Hazrati et al (2008) reported an improvementin the knowledge and performance of oncology nurses to a good and excellent level after training [16]. Additionally, TaghizadehKermani et al (2015) and Mohsen and Fareed(2013) found a significant increase inthe knowledge and performance of oncology nursesfollowing a short training course, as well as implementing the training protocol, respectively [17,18].Further, Shrestha et al (2017) suggested thatatraining intervention positively affectsthe knowledge of nurses' regarding the safe use of antineoplasticdrugs in Nepal [19]. Mahdy et al (2017) also conducted a study titled"the effect of safetyguidelines for antineoplastic drugs on the knowledge and practice of nurses in Ain al-Shams hospitals in Egypt", in which the results were consistent with the findings of the present study [20].According toKoulountiet al(2019), the nurses receiving specialized training in antineoplastic drugs represent higher performance compared to the others [21].These results were also confirmed by the studies ofBolbol et al 2019), and Angel and Soli (2017)which showed that the implementation of safetyguidelines for antineoplastic drugs has a positive effect on improving the knowledge and performance of oncology nurses and nursing students [22][23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%